(untitled) (AmeriQuests, 2021)
This issue of AmeriQuests features a selection of papers that were presented at Immigration, Cultural Participation and New Forms of Political Solidarity: Global Perspectives, held at l’Université de Liège (Belgium) in September of 2019, a few months before the outbreak of the COVID-19 global pandemic. It was the first event organized by the newly renamed Standing Committee POPADIVCIT (Popular Art, Diversity and Cultural Policies in Post-Migration Urban settings) of the European research Network IMISCOE[1]. The board of directors of the network decided in the previous spring to reorganize and rename the standing committees. POPADIVCIT became DIVCULT (Superdiversity, Migration and Cultural Change).